SEASONAL CHANGE IN BEHAVIOR OF SULFATE PARTICLES IN THE ANTARCTIC ATMOSPHERE - YAMATO, Masahiko; IWASAKA, Yasunobu; QIAN, GongWang; ONO, Akira; NISHIO, Fumihiko; FUKABORI, Masashi; OKADA, Kikuo (National Institute of Polar Research, 1990)
P(論文) Seasonal change in solar radiation possibly influences production of secondary particles through photochemical processes. The particle size distribution of sulfate particles collected at sampling site G11 (72°23′S, 32°20′E, Jan., 1987) and Mizuho Station (70°42′S, 44°20′E, Aug., 1986) showed following features. 1. Number concentration of particles in submicron size range in summer was larger than that in winter. 2. Mode of number-size distribution function of collected particles was 0.06μm in both summer and winter. 3. In summer sulfuric acid particles were predominant and the particles having radius larger than 0.3μm up to 1.8μm were present but not in winter. 4. In summer the Aitken particle number mixing ratio was larger than that in winter. Particles with radius larger than 0.3μm were rarely seen in the Antarctic marine atmosphere. In the inner Antarctic atmosphere the rain- and wash-out removal process of aerosol particles seems to be less active than in the marine atmosphere. Such atmospheric condition may enable relatively large particles to form. departmental bulletin paper